Factors Affecting Knowledge Sharing Among Academic Staff in Selected Malaysian Higher Educational Institutions and the Effect on Performance - Supar, Norizah (2006)
Knowledge is an organization's best sustainable source of competitive advantage and knowledge management is considered a key part of the strategy of using expertise to create a sustainable competitive advantage. In order to transform knowledge into a valuable organizational asset, knowledge, experience and expertise must be formalized, distributed, shared and applied. Knowledge sharing is, therefore, one of the key processes in knowledge management. The objective of this study is to expand our understanding of the factors that affect knowledge sharing among academic staff in Malaysian higher academic institutions. Its relevance to higher academic institutions is important considering that being a center of learning, a higher level of knowledge sharing among the teaching staff could bring about an increased level of productivity or performance in the workplace. The outcome of this study will enable further understanding on knowledge sharing behavior of academic staff and may, therefore, contribute towards the successful implementation of knowledge sharing as part of organizational knowledge management initiatives. Based on non-random, criterion, purposive sampling, three higher academic institutions from the Klang Valley area were selected to be included in the study. Findings from 194 respondents indicated that management support, solidarity, distributed model, knowledge sharing to be included in work process, presence of IT for the purpose of knowledge sharing and mentoring are positively related to knowledge sharing and that knowledge sharing is positively related to performance.